Feeling anxious'- women's experiences of having a baby in Australia during the COVID-19 pandemic using the Voqual real time app - Hazel Keedle; Kimberley Tomczak; Belinda Lequertier; Hannah G Dahlen (BMC, 2023)
Abstract Purpose Internationally, the COVID-19 pandemic impacted maternity services. In Australia, this included changes to antenatal appointments and the reduction of support people during labour and birth. For women pregnant during the pandemic there were increased stressors of infection in the community and in hospitals along with increased periods of isolation from friends and families during lockdown periods. The aim of this study was to explore the real-time experiences of women who were pregnant and had a baby during the first wave of the COVID-19 pandemic in Australia. Methods This study followed seven women throughout their pregnancy and early parenthood. Women created audio or video recordings in real time using the Voqual app and were followed up by in-depth interviews after they gave birth. Results Using narrative analysis their individual stories were compared and an overarching theme of 'feeling anxious' was found which was underpinned by the two themes 'model of care' and 'environment'. Conclusions These findings highlight the protective impact midwifery continuity of care has on reducing anxiety in women during the pandemic, and that the home environment can either be secure and safe or a place of isolation.